1990
DOI: 10.1207/s15327906mbr2502_1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and Modifying Covariance Structure Models: A Review and Recommendation

Abstract: The purpose of this article is to present a strategy for the evaluation and modification of covariance structure models. The approach makes use of recent developments in estimation under non-standard conditions and unified asymptotic theory related to hypothesis testing. Factors affecting the evaluation and modification of these models are reviewed in terms of nonnormality, missing data, specification error, and sensitivity to large sample size. Alternative model evaluation and specification error search strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(144 citation statements)
references
References 27 publications
2
141
0
1
Order By: Relevance
“…After correcting the coding errors in data, it is important to handle missing values properly (Kaplan, 1990;Kline, 2005). There are several missing value analysis methods (e.g., pairwise deletion, listwise deletion or series mean).…”
Section: Outliers and Missing Valuesmentioning
confidence: 99%
“…After correcting the coding errors in data, it is important to handle missing values properly (Kaplan, 1990;Kline, 2005). There are several missing value analysis methods (e.g., pairwise deletion, listwise deletion or series mean).…”
Section: Outliers and Missing Valuesmentioning
confidence: 99%
“…On the other hand, multiple relaxations of parameter constraints at Step 1 that are guided primarily by fit indexes (e.g., modification indexes) are not recommended. A number of studies have shown that repeated respecifications of this sort will fail to lead to the "true" model in many cases, and that the chosen modifications can vary widely across samples (Kaplan, 1989(Kaplan, , 1990MacCallum, 1986;MacCallum, Roznowski, & Necrowitz, 1992). Our view is that if modifications to the Step-1 model are introduced in this manner, the resulting modified model should be regarded as an exploratory creation that will need confirmation in future samples.…”
Section: Step 1: the Unrestricted Modelmentioning
confidence: 99%
“…Kaplan, 1990). Structural modeling allows statistical testing of the fit of hypothesized models against actual empirical data sets (Bentler, 1990;Connell, 1987;Tanaka, 1987).…”
Section: Advantages Of Structural Equation Modelingmentioning
confidence: 99%